Effect of Financial Target, Ineffective Monitoring, and Whistleblowing Systems on Fraudulent Financial Reporting - Apriliana Anami Lestari; Dian Widiyati (Journal of Industrial Engineering & Management Research, 2023)
This study aims to determine and empirically test the effect of financial targets, ineffective monitoring, and whistleblowing systems on fraudulent financial reporting with earnings management proxies. The data used in this research is secondary data. The population uses the health sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the research year 2017-2021. The sampling technique was purposive sampling so that the research sample obtained was 12 companies. Hypothesis testing using multiple linear analysis with Eviews10 application software. The results of this study indicate that financial targets and ineffective monitoring have a significant positive effect on indications of financial statement fraud, while the whistleblowing system has a negative effect on indications of financial statement fraud.